2015
DOI: 10.1111/jace.13978
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for Macro Porous RB‐SiC Derived from SiC/Novolac‐type Phenolic Composite

Abstract: A novel fabrication route to make macroporous silicon carbide (SiC) has been proposed in this study. The route is composed of the following two steps: the fabrication of porous a-SiC/novolac-type phenolic composite using hexamethylenetetramine (HMT) as a curing/blowing agent for the novolac monomer and a conventional reaction-bonded (RB) sintering of the composite. The a-SiC/novolac-type phenolic composite was carbonized at 800°C for 2 h in N 2 gas and then reacted with the molten silicon at 1450°C for 30 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…However, loading of silicon sufficient for siliconization of carbon produced from the pitch is very difficult due to the high carbon yield (80–90 wt%) of the pitch. Shimamura et al reported a reaction bonding approach for the preparation of SiC foams from novolac phenolic resin and SiC powder . In this, carbon–SiC composite foams were obtained by carbonization of novolac resin–SiC powder composite foam bodies prepared by the foaming of novalac resin–SiC powder compacts using hexamethylenetetramine as a blowing agent.…”
Section: Introductionmentioning
confidence: 99%
“…However, loading of silicon sufficient for siliconization of carbon produced from the pitch is very difficult due to the high carbon yield (80–90 wt%) of the pitch. Shimamura et al reported a reaction bonding approach for the preparation of SiC foams from novolac phenolic resin and SiC powder . In this, carbon–SiC composite foams were obtained by carbonization of novolac resin–SiC powder composite foam bodies prepared by the foaming of novalac resin–SiC powder compacts using hexamethylenetetramine as a blowing agent.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that blowing was observed above a novolac-HMT content of 60 vol%, while pore coarsening occurred at 80 vol%. 15) The content of the novolac-HMT was thus fixed at 60 vol% in this study. The mixed alumina powder was blended with novolac-HMT powder (SP1101 novolac type with 9 wt.% of curing agent: HMT, D 50 = 24.8¯m; Asahi Organic Chemicals Industry Co. Ltd., Tokyo, Japan) at a volume ratio of 40:60 (mixed alumina:novolac-HMT) for one hour under dry conditions by a V-type mixer.…”
Section: Experiments and Characterizationmentioning
confidence: 99%
“…We have previously proposed a direct-foaming approach for porous ceramics from ceramic/novolacHexaMethyleneTetramine (HMT) composite, 9), 10) and using this approach we have fabricated porous alumina with the relatively dense surface layer. 11) In this study, HMT was used as a blowing agent and as a curing one for the novolac resin.…”
mentioning
confidence: 99%